Community-Based Web-Learning Media for Disaster Mitigation Understanding of University Students - Tengku Muhammad Sahudra; Ary Kiswanto Kenedi; Asnawi; Imam Hadi Sutrisno; Teguh Ardiansyah; Ilpa Ardani Br Sitepu (Jurnal Edutech Undiksha, 2024)
Indonesia, disasters frequently occur, so a good understanding of disaster mitigation is needed. Researchers have developed a learning innovation in previous research to increase students' understanding of disaster mitigation. This innovation is in the form of community-based web-learning. This web learning has been declared suitable for use. Further studies are needed to determine the impact on students' understanding of disaster mitigation. This research aims to analyze the effect of community-based web-learning on higher education students' understanding of disaster mitigation. This research uses a quasi-experimental design using a non-equivalent control-group design. The research sample consisted of 200 university students. Students' understanding of disaster mitigation is measured using an essay test. The data analysis process uses the SPSS 26 application, including descriptive tests, normality tests, homogeneity tests, paired sample t-tests, and independent t-tests. The research results found a significant difference in the average understanding of disaster mitigation for university students who studied using community-based web-learning media and those who studied using conventional learning models. Students who use web-based learning have a higher average than those who study in conventional classes. This result proves that community-based web learning can increase higher education students' understanding of disaster mitigation.